The Effect of Business Intelligence System Implementation on Organizational Performance in the Digital Age - Judijanto, Loso; Zulkifli, Zulkifli; Yusniar, Yusniar (Westscience Press, 2024)
The implementation of Business Intelligence systems has emerged as one of the key strategies to enhance organizational performance in the digital era. This study systematically reviews 17 peer-reviewed articles from the Scopus database to examine the impact of BI systems on various performance dimensions, including operational efficiency, decision-making, financial outcomes, and customer satisfaction. Results indicated that BI systems enhance organizational agility and competitiveness, while data quality, management support, user training, and strong IT infrastructure were among the factors that drive their success. Challenges such as high implementation costs, resistance to change, and integration complexities remain. Emerging trends in AI integration, cloud-based solutions, and real-time analytics reflect the evolving possibilities of BI systems. This research contributes to the literature by synthesizing critical insights and offering actionable recommendations for practitioners and researchers aiming to leverage BI systems for sustained organizational growth.